Development of Toilet Training based on Augmented Reality for Children with Autism Spectrum Disorder - Widi Kumara Jaga Paramuditha; Rahmahtrisilvia Rahmahtrisilvia; Risca Amani (Universitas Pendidikan Ganesha, 2025)
Toilet training is a basic skill in the growth and development process of children with Autism Spectrum Disorder (ASD). The process of toilet training usually uses traditional conventions that often rely heavily on auditory instructions, and a lack of visual support. ASD children are visual learners so they have difficulty in understanding verbal instructions. This research aims to develop augmented reality-based interactive learning media that supports the audiovisual learning style of ASD children. This research uses a prototype method by identifying problems, analyzing user needs, designing product designs, making products, and expert testing. The subjects involved in this study are teachers, children of ASD and expert validators. The data collection techniques used were observation and interviews to see the empirical conditions of toilet training learning using observation instruments and interview instruments. Then use a questionnaire to validate the product created. The data was analyzed qualitatively descriptively for the results of interviews and observations, while quantitative data for the results of the expert validator questionnaire. The result of this research is in the form of an augmented reality-based toilet training application with a marker card as a barcode to integrate 3-dimensional visual elements that have been validated by experts. So this is one of the interactive media in teaching toilet training to ASD children. This application can be accessed using a smartphone so that it can not only be taught at school, but also at home.